CASH CROPS VERSUS FOOD CROPS IN AFRICA: A Conflict between Dependency and Autonomy - Ould-Mey, Mohameden (حوليات كلية الآداب والعلوم الإنسانية, 2026)
The article examines the conflict between export-oriented cash-crop production and food-crop production in African agriculture. It stresses agriculture’s central role in African economies and links current food dependency and rural poverty to colonial policies that redirected land, labour, credit, and infrastructure toward crops demanded by external markets. The study discusses the continuing influence of this structure after independence, the social differentiation it created, and the role of governments, international institutions, and local elites in maintaining export-led agricultural policies. It also contrasts approaches associated with the World Bank and the Organization of African Unity regarding agricultural development and food security. The article argues that dependence on a limited number of export crops, external markets, imported food, and foreign inputs has deepened economic vulnerability and inequality, while weakening local food production and self-sufficiency (*).